A Theoretical and Experimental View on the Temperature Dependence of the Electronic Conduction through a Schottky Barrier in a Resistively Switching SrTiO3‐Based Memory Cell. (14th June 2018) - Funck, Carsten; Marchewka, Astrid; Bäumer, Christoph; Schmidt, Peter C.; Müller, Phillip; Dittmann, Regina; Martin, Manfred; Waser, Rainer; Menzel, Stephan
Abstract: Metal–semiconductor Schottky interfaces are of high interest in many fields of semiconductor physics. One type of electronic devices based on Schottky contacts are resistive switching cells. The mostly applied analytical models are insufficient to describe all Schottky contact systems, which further impedes finding the correct conduction mechanism and may lead to physical misunderstandings. In this work, the electron transport properties of the resistively switching SrTiO3 /Pt interface model system are investigated using a combination of experimental and theoretical methods. Temperature‐dependent I–V curves are measured and analyzed using an analytical approach, an atomistic approach based on density functional theory and the nonequilibrium Green's function formalism, and a continuum modeling approach. The findings suggest two different conduction mechanisms. Instead of a current transport over the barrier, as in the case of Schottky emission theory, the simulations show that tunneling through the Schottky barrier dominates. In the low voltage range, only thermally excited electrons can tunnel into the conduction band. For higher voltages, the SrTiO3 conduction band and the Fermi level at the injecting Pt‐electrode are aligned, allowing also electrons at the Fermi‐edge to tunnel. Consequently, the temperature dependence changes, leading to a crossing of the I – V curves at different temperatures. Abstract : In this study, a thorough investigation of the current transport across a Schottky junction in resistive switching devices is presented. It shows that the popular approach of using analytical equations is not sufficient to explain the transport across these devices. In detail, our single‐band transport simulations and quantum mechanical density functional theory calculations reveal a thermally assisted tunnelling transport mechanism.